2016
DOI: 10.1111/acel.12455
|View full text |Cite
|
Sign up to set email alerts
|

Cellular senescence impact on immune cell fate and function

Abstract: SummaryCellular senescence occurs not only in cultured fibroblasts, but also in undifferentiated and specialized cells from various tissues of all ages, in vitro and in vivo. Here, we review recent findings on the role of cellular senescence in immune cell fate decisions in macrophage polarization, natural killer cell phenotype, and following T‐lymphocyte activation. We also introduce the involvement of the onset of cellular senescence in some immune responses including T‐helper lymphocyte‐dependent tissue hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
116
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 93 publications
2
116
0
3
Order By: Relevance
“…It would be interesting to verify whether NK cell number negatively correlates with senescent cell accumulation in aging tissues. Cells of the immune system, including NK cells, display a senescent phenotype with increasing age, a process called immunosenescence . The idea of ameliorate aged tissue functionality by killing senescent cells is supported by different studies …”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to verify whether NK cell number negatively correlates with senescent cell accumulation in aging tissues. Cells of the immune system, including NK cells, display a senescent phenotype with increasing age, a process called immunosenescence . The idea of ameliorate aged tissue functionality by killing senescent cells is supported by different studies …”
Section: Discussionmentioning
confidence: 99%
“…Senescent cells accumulate in various tissues and organs with aging (Campisi, 2005). Senescent cells have been demonstrated to disrupt tissue structure and function through the secretion of pro‐inflammatory cytokines, chemokines, and proteases, a feature termed the senescence‐associated secretory phenotype (Campisi & d'Adda, 2007; Vicente, Mausset‐Bonnefont, Jorgensen, Louis‐Plence, & Brondello, 2016). Recent studies have demonstrated that selectively eliminating senescent cells can attenuate several age‐dependent disorders (Baker et al., 2011; Chang et al., 2016; Roos et al., 2016; Zhu et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…5 The factors that contribute to acute GVHD are not well understood, although this patient had bidirectional donor-recipient HLA class I and II mismatches which may support immune surveillance of the lung allograft. Abnormally low telomerase activity is associated with impaired immunosurveillance and defective cell-mediated immunity, 6 and this report suggests that loss-of-function mutations in telomerase may reduce the ability to effectively eliminate donor immune cells in lung grafts.…”
Section: Discussionmentioning
confidence: 79%